2014
DOI: 10.2217/cns.13.63
|View full text |Cite
|
Sign up to set email alerts
|

Modern cerebrospinal fluid analyses for the diagnosis of diffuse large B-cell lymphoma of the CNS

Abstract: CNS lymphomas represent rare and aggressive variants of extranodal non-Hodgkin's lymphomas, which may present with diverse neurological symptoms and are often diagnostically challenging. Primary CNS lymphomas develop within the CNS and characteristically involve the brain, leptomeninges, eyes and, in rare cases, spinal cord. Secondary CNS lymphomas are characterized by expansion of systemic lymphomas to the CNS. Multimodal investigation of cerebrospinal fluid (CSF) comprises an important component of the diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…This is because PCNSL is particularly chemo-and radiosensitive. Conversely, gross total resection is the gold standard in the management of meningiomas and gliomas (Baraniskin & Schroers, 2014;Gordon et al, 2011;Hoang-Xuan et al, 2015;Korfel & Schlegel, 2013;Muñiz et al, 2014). The same principle applies for steroid administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because PCNSL is particularly chemo-and radiosensitive. Conversely, gross total resection is the gold standard in the management of meningiomas and gliomas (Baraniskin & Schroers, 2014;Gordon et al, 2011;Hoang-Xuan et al, 2015;Korfel & Schlegel, 2013;Muñiz et al, 2014). The same principle applies for steroid administration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly in our case, the initiation of high-dose dexamethasone did not affect our diagnosis. The typical diagnostic workup for CNS lymphoma consists of CSF analysis for markers such as IL-10, CXCL13, CD19, CD20 or flow cytometry (Baraniskin et al, 2011;Baraniskin & Schroers, 2014;Muñiz et al, 2014;Rubenstein et al, 2013). Due to the mass effect that is exerted by meningiomas, CSF analysis is difficult without a craniotomy as a lumbar puncture would not be recommended in such a setting.…”
Section: Discussionmentioning
confidence: 99%
“…CSF cytology, in which CSF is examined under a microscope to look for neoplastic cells (presence or absence) is currently considered the gold standard test for diagnosis, tumor staging, and therapy decisions in many types of cancer such as medulloblastoma, lymphoma, and metastatic carcinomas [ 65 ]. Although indispensable, this method bears neither quantification nor molecular analysis of tumor cells, lacks sensitivity and assignment to a particular tumor is often not possible [ 65 , 66 , 67 ].…”
Section: Cerebrospinal Fluid (Csf) As Diagnostic Window For the Pamentioning
confidence: 99%
“…To maximize the chances of finding brain cancer markers in the CSF, it has been realized that it is necessary to detect changes at the molecular level rather than waiting for a macroscopic tumor to emerge [ 65 ]. Various methods and new technologies are being tested for in vitro assessment of CSF looking for potential markers for CNS cancers including: proteochemical and immunophenotypic studies by flow cytometry (that provides information about cell surface protein expression), molecular genetic analyses of CSF [ 67 ], immunocytochemistry, immunoglobulin heavy chain (IgH) rearrangement which analyzes the clonality of the antibodies being produced, polymerase chain reaction, fluorescence in-situ hybridization (FISH), DNA single cell cytometry, capillary electrophoresis and mass spectrometry reviewed in [ 4 , 65 ]. Proteomic profiling of CNS malignancies has revealed that free immunoglobulin light chains and antithrombin III, a serine protease inhibitor that is associated with neo-vascularization, are differentially expressed in some brain cancers [ 68 , 69 ].…”
Section: Cerebrospinal Fluid (Csf) As Diagnostic Window For the Pamentioning
confidence: 99%
See 1 more Smart Citation